Networked graphics : building networked games and virtual environments - Steed, Anthony; Oliveira, Manuel Fradinho (Burlington, MA : Morgan Kaufmann ; Oxford : Elsevier Science [distributor], 2010)
This broad-ranging book equips programmers and designers with a thorough grounding in the techniques used to create truly network-enabled computer graphics and games. Written for graphics/game/VE developers and students, it assumes no prior knowledge of networking. The text offers a broad view of what types of different architectural patterns can be found in current systems, and readers will learn the tradeoffs in achieving system requirements on the Internet. The book explains the foundations of networked graphics, then explores real systems in depth, and finally considers standards and extensions. Numerous case studies and examples with working code are featured throughout the text, covering groundbreaking academic research and military simulation systems, as well as industry-leading game designs.
PART I GROUNDWORK -- CHAPTER 1 Introduction -- CHAPTER 2 One on One (101) -- CHAPTER 3 Overview of the Internet -- CHAPTER 4 More Than Two -- PART II FOUNDATIONS -- CHAPTER 5 Issues in Networking Graphics -- CHAPTER 6 Sockets and Middleware -- CHAPTER 7 Middleware and Message-Based Systems -- CHAPTER 8 Middleware and Object-Sharing Systems -- CHAPTER 9 Other Networking Components -- PART III REAL SYSTEMS -- CHAPTER 10 Requirements -- CHAPTER 11 Latency and Consistency -- CHAPTER 12 Scalability -- CHAPTER 13 Application Support Issues.
Includes bibliographical references and index.
1
Keywords: Computer games -- Programming; Computer graphics; Virtual reality